2016
DOI: 10.1007/s00383-016-3880-7
|View full text |Cite
|
Sign up to set email alerts
|

The value of contrast studies in the evaluation of bowel strictures after necrotising enterocolitis

Abstract: Colon is the commonest site for post-NEC stricture and contrast enema is the study of choice for detecting these strictures prior to stoma closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…[20,21] Intestinal strictures develop in 9% to 32% of patients who underwent operation. [4,20,22,23] A contrast study (conventional contrast enema, distal loop enema, or both) is recommended to rule out strictures or complete obstruction before reestablishment of intestinal continuity. Koike et al [24] reported that LBW infants might get benefits from enteral refeeding.…”
Section: Discussionmentioning
confidence: 99%
“…[20,21] Intestinal strictures develop in 9% to 32% of patients who underwent operation. [4,20,22,23] A contrast study (conventional contrast enema, distal loop enema, or both) is recommended to rule out strictures or complete obstruction before reestablishment of intestinal continuity. Koike et al [24] reported that LBW infants might get benefits from enteral refeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its high sensitivity, the contrast enema may still miss strictures that are present. When a sufficient amount of contrast does not pass through the ileocecal valve, small bowel strictures can remain undiagnosed (10). Contrast studies were performed in all the patients in our study.…”
Section: Discussionmentioning
confidence: 98%
“…These studies may include contrast enemas, distal loopograms, or both. The sensitivity and specificity of the contrast enema are 93% and 88%, respectively, and for the distal loopogram, they are 50% and 96%, respectively (10,11). Despite its high sensitivity, the contrast enema may still miss strictures that are present.…”
Section: Discussionmentioning
confidence: 99%
“…Prematurity, central line access and prolonged parenteral nutrition contribute to increased incidence of septic complication [19]. Intestinal strictures develop in 9-32% of patients who underwent the operation [20]. Stricture occurred after both medical and surgical treatment for NEC and in both functional and defunctionalized bowel.…”
Section: Discussionmentioning
confidence: 99%